Review : Enterocyn from Enterococcus Genus as a Probiotic, Antimicrobial and Biopreservative - Alang, Hasria (Pharmauho: Jurnal Farmasi, Sains, dan Kesehatan, 2020)
Lactic acid bacteria (LAB) is agras, produces antimicrobial compounds called bacteriocin. It can reduce its dependence on antibiotic use. Enterococcus is one of member LA.B. This bacterium has a short and paired chain shape and produces bacteriocin called enterocin. This compound can inhibit the growth of pathogenic microbes that cause disease and food spoilage, so that it can be used as an antimicrobial and biopreservative and also as a probiotic candidate. The use of Enterococcus as a probiotic and biopreservative is often disputed. However, some studies suggest that cases of bacteremia and urinary tract infections by the genus only occur in people who have immune compromised and enterococcus that have been resistant to vancomycin.